Bagaiamana Pendidikan Akuntansi Memastikan Relevansinya dengan Profesional Akuntan di Masa Depan? - Rino Tam Cahyadi; Cecilia Deandra Christina Indranatan; Fulvian Wahyu Danendra Mangkuluhur; Bagas Brian Pratama (JOURNAL OF APPLIED MANAGERIAL ACCOUNTING, 2025)
This study aims to develop an accounting education model that is adaptive to digital technological changes and the learning characteristics of Generation Z. The main issue addressed is the gap between the competencies of accounting graduates and the increasingly digitalized demands of the industry, as well as the limited relevance of conventional teaching approaches to the learning styles of digital-native students. A mixed methods approach with an exploratory-explanatory design was employed across three stages: (1) conceptual model development through a scoping literature review, (2) industry needs exploration via interviews with six accounting professionals from both the private and public sectors, and (3) empirical implementation and evaluation of the model within classroom-based accounting courses. The literature review and expert interviews concluded that the accounting education model must undergo changes to be relevant to the future industry. These changes encompass three key elements: integrating digital technology, contextual learning based on practical problems, and the role of lecturers as facilitators. This model was then tested in classroom learning among three different accounting student cohorts at Ma Chung University, with a total of 72 accounting students. The evaluation of the model's implementation demonstrated a high level of satisfaction with an average response of 4.3 (very satisfied), as well as high instrument reliability with a Cronbach's Alpha value of >0.95. This research provides a framework for future accounting education reform that is more contextual and aligned with industry demands and the character of future students.